An exploration of the feasibility and clinical value of half-dose 5-h total-body 18F-FDG PET/CT scan in patients with Takayasu arteritis. - Adili, Dilibire; Cai, Danjie; Wu, Bing; Yu, Haojun; Gu, Yushen; Zhang, Yiqiu; Shi, Hongcheng (European Journal of Nuclear Medicine & Molecular Imaging, 2023)
Purpose: To explore the feasibility and clinical value of 5-h delayed 18F-fluorodeoxyglucose (18F-FDG) total-body (TB) positron emission tomography/computed tomography (PET/CT) in patients with Takayasu arteritis (TA). Methods: This study included nine healthy volunteers who underwent 1-, 2.5-, and 5-h triple-time TB PET/CT scans and 55 patients with TA who underwent 2- and 5-h dual-time TB PET/CT scans with 1.85 MBq/kg 18F-FDG. The liver, blood pool, and gluteus maximus muscle signal-to-noise ratios (SNRs) were calculated by dividing the SUVmean by its standard deviation to evaluate imaging quality. TA lesions' 18F-FDG uptake was graded on a three-point scale (I, II, III), with grades II and III considered positive lesions. Lesion-to-blood maximum standardised uptake value (SUVmax) ratio (LBR) was calculated by dividing the lesion SUVmax by the blood pool SUVmax. Results: The liver, blood pool, and muscle SNR of the healthy volunteers at 2.5- and 5-h were similar (0.117 and 0.115, respectively, p = 0.095). We detected 415 TA lesions in 39 patients with active TA. The average 2- and 5-h scan LBRs were 3.67 and 7.59, respectively (p < 0.001). Similar TA lesion detection rates were noted in the 2-h (92.0%; 382/415) and 5-h (94.2%; 391/415) scans (p = 0.140). We detected 143 TA lesions in 19 patients with inactive TA. The 2- and 5-h scan LBRs were 2.99 and 5.71, respectively (p < 0.001). Similar positive detection rates in inactive TA were noted in the 2-h (97.9%; 140/143) and 5-h (98.6%; 141/143) scans (p = 0.500). Conclusion: The 2- and 5-h 18F-FDG TB PET/CT scans had similar positive detection rates, but both combined could better detect inflammatory lesions in patients with TA.